Analisis Pengaruh Brand Image, Promosi, Keterjangkauan Harga dan Cita Rasa Terhadap Pembelian Ulang: Studi Kasus pada Restoran Wizzmie di Kota Semarang - Muhammad Amin Nabawi; Harries Arizonia Ismail (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of brand image, promotion, price affordability, and taste on repurchase decisions at Wizzmie Restaurant in Semarang City. The research is based on the importance of repurchase behavior as an indicator of customer loyalty, which contributes to business sustainability. Brand image, attractive promotions, affordable prices, and consistent taste are believed to be the key factors that encourage customers to make repeat purchases. The research method used is a quantitative approach with multiple linear regression analysis. Data were collected through questionnaires distributed to 100 respondents who had made at least two purchases at Wizzmie Restaurant. The sampling technique used was purposive sampling. Validity and reliability tests were conducted to ensure the quality of the collected data. The results show that brand image, promotion, price affordability, and taste simultaneously have a significant influence on repurchase behavior. Partially, brand image, price affordability, and taste have a positive and significant influence, while promotion does not have a significant effect. These findings provide strategic implications for Wizzmie Restaurant management in enhancing customer loyalty through improving product quality and brand perception.